Structural Determination And Analysis Of Some New Schiff Base And Triangulo-Triruthenium Compounds - Yeap , Chin Sing (2011)
Eight Schiff base compounds were studied in this research. They crystallized out in the common space groups, i.e. four compounds are in monoclinic C2/c, and one each in monoclinic Cc, P21 and Pn and triclinic1P. One Schiff base compound exists in a zwitterion form. The structures of two Schiff base compounds are disordered. One Schiff base compound is a racemic twin crystal. Water solvent exists in the asymmetric unit of two Schiff base compounds. The Schiff base compounds all exist in an E configuration with respect to the N=C. The average N=C double bond value is 1.282 Å.